2017
DOI: 10.2196/jmir.6655
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Child Health: Exploring the Use of Social Media to Engage Parents in Patient-Centered Outcomes Research

Abstract: BackgroundWith the rapid growth of technology and its improved accessibility globally, social media is gaining an increasingly important role in health care. Patients are frequently engaging with social media to access information, share content, and interact with others in online health communities. However, the use of social media as a stakeholder engagement strategy has been minimally explored, and effective methods for involving participants in research on the identification of patient-centered outcomes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 37 publications
1
37
1
Order By: Relevance
“…Almost all of our respondents declared that they performed health-related searches on the website. Our figures are larger than the ones reported by other authors [30,31], but we should consider that our respondents accessed our questionnaire from a pediatric health web, so they probably are Internet active users, and they probably are concerned with the health of their children.…”
Section: Demographical Datacontrasting
confidence: 64%
“…Almost all of our respondents declared that they performed health-related searches on the website. Our figures are larger than the ones reported by other authors [30,31], but we should consider that our respondents accessed our questionnaire from a pediatric health web, so they probably are Internet active users, and they probably are concerned with the health of their children.…”
Section: Demographical Datacontrasting
confidence: 64%
“…A variety of recruitment methods was advisable, tailored to reach each stakeholder group. Nevertheless, social media platforms are perhaps most effective only if they are already established rather than being set up specifically for the COS development project, or if the target audience are known to be typical social media users [ 36 ]. Although there is substantial interest in the use of social media as a component of an effective patient recruitment strategy, challenges regarding engagement, representativeness, obtaining buy-in, and resources required have been noted.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed account of the traffic to the survey and usability are available in our published process evaluation. 18 …”
Section: Resultsmentioning
confidence: 99%
“…One variable of interest in this study was the reach of social media as a recruitment strategy (reported elsewhere 18 ); therefore, the sample size was an outcome, rather than a predefined condition. To accommodate this, we did not define the number of participants a priori, instead allowing the detail that emerged from our data collection to guide the extent of recruitment.…”
Section: Methodsmentioning
confidence: 99%